Lithosphere density structure of southeastern South America sedimentary basins from the analysis of residual gravity anomalies - Moura, Denise Silva de; Marangoni, Yára Regina (Frontiers in Earth Science, 2023)
We conduct a gravity study of the lithosphere beneath three large sedimentary basins in southeastern South America: Paraná, Chaco-Paraná, and Pantanal. We compile a massive gravity database and estimate the free-air and Bouguer gravity anomalies, resulting in a novel complete Bouguer anomaly map for the study area. To discern the influence of crustal loads with known lithologies, including sediments, basalts, and topography variations of the Moho discontinuity, we calculate their gravity effects and subsequently remove them from the complete Bouguer anomaly, leading to the development of our residual Bouguer anomaly map. This map highlights unknown anomalous masses within the lithosphere. To aid in the interpretation of these residual anomalies, we perform a 2D forward modeling. Based on our results, we propose new boundaries for the Paranapanema block and the Luiz Alves craton. Additionally, we propose that the Ponta Grossa swarm dike has a more substantial impact on the crust and lithosphere than previously considered, and delimit the region of influence of this magmatism in the lithosphere. Moreover, tectonic features such as the São Francisco paleocontinent and the Rio de La Plata craton appear to be associated with negative residual Bouguer anomaly regions. Furthermore, we identify and emphasize the significance of the Western Paraná Suture, which acts as a demarcation between the Paraná Basin region and the Pantanal and Chaco-Paraná basins. Remarkably, this suture appears to play a more important role in shaping the density structure of the southwest of South America than the age and tectonic history of the sedimentary basins.